Using solar energy and optimizing energy consumption in commercial buildings - Mohit Mafi, Sahar; Ghara Khany, Alireza (Revista Publicando, 2018)
Considering the energy issue is one of the main issues of recent decades, both in terms of contamination and in terms of resource constraints so, as much as possible, should prevent fromenergy loss. Solar power generation with photovoltaic is one of the clean energy methods that use of photovoltaic plates and dynamic forces such as wind are the right ways to achieve this goal. In these buildings, photovoltaic panels will be considered part of the outer shell of the building in the process of architectural design which inthe back of these plates, dynamic structures will be placed in order to displacement of plates and Confronting with lateral forces such as wind. If this loading is affected by a non- uniform wind or earthquake dynamically, the structure begins to vibrate in various vibration modes. Hence, by expressing solar radiation calculation models, first, the selected model is fully introduced and then, using this model, a combination of photovoltaic and dynamic structures with a building in Tehran have been determined the amount of radiation received from the sun on different surfaces and wind speed. In the end it was concluded that a construction could be made to provide the largest amount of heating and cooling needs from the sun’s energy a dynamic system can also help to maximize its efficiency.